If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 50x + -2 = 48 Reorder the terms: -2 + 50x = 48 Solving -2 + 50x = 48 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 50x = 48 + 2 Combine like terms: -2 + 2 = 0 0 + 50x = 48 + 2 50x = 48 + 2 Combine like terms: 48 + 2 = 50 50x = 50 Divide each side by '50'. x = 1 Simplifying x = 1
| y=4-3+-3 | | -7=4c+7c-2c | | y=4-34 | | 3x^2+8x-4=0 | | x*x-x-2=0 | | 4y+7= | | -x*x-14x-50=0 | | 12+36=13y-17y | | 5h+13=13 | | 4x-34=345 | | 7p-2p-p= | | 40=8-16k | | x*x+5x+6=0 | | -3x^2-8x+4=0 | | -3x-8x+4=0 | | 7x*x-54x+35=0 | | 5x-3x+6=56 | | 30=5x+5 | | 8x=-17 | | 29x=0 | | x*x-2x-3=0 | | 5x-3x=4+10 | | x*x+7x+6=0 | | 2x+3x+5x=20 | | 3(3x+6)=3(x+8) | | -x*x-6x-5=0 | | 12+5(9-7X)=9-11X | | x^2+25x+196=0 | | 4+e=4 | | 2p+32=14p | | 2n+34=14p | | x+-2=5 |